INVESTIGATING THE RELATIONSHIP BETWEEN LIPID PROFILES AND POTENTIAL RISK REDUCTION OF ATHEROSCLEROTIC CARDIOVASCULAR DISEASE IN DIABETIC INDIVIDUALS. - Dr. Sidra Shah; Dr Muhammad Sannan; Dr Talal Safdar; Dr Adeela Kosar Bajwa; Dr Arshad Ali; Dr Mahboob Ur Rehman (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives:To assess the effectiveness of Lipid therapy in lowering atherosclerotic cardiovascular disease (ASCVD) risk in Diabetic individualsMaterials and Methods:  This prospective cohort study was conducted at Department of Medicine, Khyber Teaching Hospital, Peshawar from July, 2023 to December, 2023 in which a total of 99 patients were enrolled after fulfilling the inclusion criteria. 5 ml blood was taken from all the patients and sent for lipid profile tests to check total cholesterol, LDL, HDL, and Tg. All the patients were then prescribed Statin therapy. All the patients were followed after 6 month of treatment to see the incidence of atherosclerotic cardiovascular disease (ASCVD).Results: In this study, 99 patients, with a mean age of 51.64±12.52 years, were enrolled. Prior to treatment, the mean levels of LDL, HDL, and triglycerides were 114.42±9.96 mg/dL, 43.46±6.71 mg/dL, and 129.66±22.09 mg/dL, respectively. The mean HbA1C (%) value was 8.05±0.96. Among our study participants, 8 individuals (8.1%) experienced ASCVD. There is week positive correlation between ASCVD and LDL cholesterol, HDL cholesterol and Triglycerides in DM patients with statin medication after 6 month.Conclusion: The study's findings concluded that people with a high risk of heart disease could see benefits from using statins. Further studies was recommended in order to see the effect of statin in lowering LDL cholesterol more clearly.